White striping and woody breast myopathies in the modern poultry industry: a review - Kuttappan, V. A.; Hargis, B. M.; Owens, C. M. (Poultry science, 2016)
Myopathies are gaining the attention of poultry meat producers globally. White Striping (WS) is a condition characterized by the occurrence of white striations parallel to muscle fibers on breast, thigh, and tender muscles of broilers, while Woody Breast (WB) imparts tougher consistency to raw breast fillets. Histologically, both conditions have been characterized with myodegeneration and necrosis, fibrosis, lipidosis, and regenerative changes. The occurrence of these modern myopathies has been associated with increased growth rate in birds. The severity of the myopathies can adversely affect consumer acceptance of raw cut up parts and/or quality of further processed poultry meat products, resulting in huge economic loss to the industry. Even though gross and/or histologic characteristics of modern myopathies are similar to some of the known conditions, such as hereditary muscular dystrophy, nutritional myopathy, toxic myopathies, and marbling, WS and WB could have a different etiology. As a result, there is a need for future studies to identify markers for WS and WB in live birds and genetic, nutritional, and/or management strategies to alleviate the condition.